2009
DOI: 10.1590/s0102-09352009000600008
|View full text |Cite
|
Sign up to set email alerts
|

Análise computacional da compactação da cromatina de espermatozoides de galo

Abstract: RESUMOTestaram-se variantes metodológicas utilizando azul de toluidina (AT), até se estabelecer um protocolo confiável para a avaliação computacional da compactação da cromatina em espermatozoides de galo. Para tal, foram utilizados sêmen de 10 galos com 35 semanas de idade e sêmen de 10 galos com 60 semanas de idade. O melhor método foi o de hidrólise com ácido clorídrico 1N por 10 minutos, coloração em cubeta com AT 0,025%, pH 4,0, por 20 minutos, desidratação em álcool, diafanização em xilol e montagem com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
0
12
0
4
Order By: Relevance
“…However, in contrast with the data from other species, there are still only few studies of rooster semen; thus, there is still no reliable parameters for analysis (LUCASZEWICZ et al, 2008;ARRUDA et al, 2011). On the other hand, the semen of old roosters has been observed to have higher degree of chromatin changes than that of young roosters, which may decrease their fertility, even in the absence of changes in the semen physical characteristics (RODRIGUES et al, 2009). Bergstein et al (2014) reported that although sperm motility and membrane integrity tests are important, these may not reveal relevant sperm lesions.…”
Section: Resultsmentioning
confidence: 99%
“…However, in contrast with the data from other species, there are still only few studies of rooster semen; thus, there is still no reliable parameters for analysis (LUCASZEWICZ et al, 2008;ARRUDA et al, 2011). On the other hand, the semen of old roosters has been observed to have higher degree of chromatin changes than that of young roosters, which may decrease their fertility, even in the absence of changes in the semen physical characteristics (RODRIGUES et al, 2009). Bergstein et al (2014) reported that although sperm motility and membrane integrity tests are important, these may not reveal relevant sperm lesions.…”
Section: Resultsmentioning
confidence: 99%
“…A study in roosters showed larger sperm head area in younger males due to increased morphological abnormalities [34]. In contrast, older boars showed spermatozoa with larger head area than their younger counterparts [35].…”
Section: Discussionmentioning
confidence: 99%
“…Among these tests, SCSA is the most used (Beletti, 2013), but its high cost lowers its practical applicability. The toluidine blue technique is easy and inexpensive (Beletti and Mello, 2004;Erenpreiss et al, 2004), and it has been used for chromatin stability evaluation of many species: humans (Erenpreiss et al, 2001;Beletti and Costa, 2003;Erenpreiss et al, 2004), rabbit (Beletti and Mello, 2004), bovine, caprine, ovine, canine (Beletti and Costa, 2003), fowl (Rodrigues et al, 2009), equine (Naves et al, 2004) and porcine (Arraztoa et al, 2016). The toluidine blue technique was chosen for the present study because spermatozoa head morphology, morphometry, and chromatin can all be evaluated concomitantly, as described by Beletti et al (2005).…”
Section: Discussionmentioning
confidence: 99%